Acutely increased aquaporin-4 exhibits more potent protective effects in the cortex against single and repeated isoflurane-induced neurotoxicity in the developing rat brain. (4th May 2023) - Yılmaz, Habip; Şengelen, Aslıhan; Demirgan, Serdar; Paşaoğlu, Hüsniye Esra; Çağatay, Melike; Erman, İbrahim Emre; Bay, Mehmet; Güneyli, Hasan Cem; Önay-Uçar, Evren
Abstract: Damage to hippocampus, cerebellum, and cortex associated with cognitive functions due to anesthetic-induced toxicity early in life may cause cognitive decline later. Aquaporin 4 (AQP4), a key protein in waste clearance pathway of brain, is involved in synaptic plasticity and neurocognition. We investigated the effects of single and repeated isoflurane (Iso) anesthesia on AQP4 levels and brain damage. Postnatal-day (P)7 Wistar albino rats were randomly assigned to Iso or Control (C) groups. For single-exposure, pups were exposed to 1.5% Iso in 30% oxygenated-air for 3-h at P7 (Iso1 ). For repeated-exposure, pups were exposed to Iso for 3 days, 3-h each day, at 1-day intervals (P7 + 9 + 11) starting at P7 (Iso3 ). C1 and C3 groups received only 30% oxygenated-air. Based on HE-staining and immunoblotting (Bax/Bcl-2, cleaved-caspase3 and PARP1) analyses, Iso exposures caused a higher degree of apoptosis in hippocampus. Anesthesia increased 4-hydroxynonenal (4HNE), oxidative stress marker; the highest ROS accumulation was determined in cerebellum. Increased inflammation (TNF-α, NF-κB) was detected. Multiple Iso-exposures caused more significant damage than single exposure. Moreover, 4HNE and TNF-α contributed synergistically to Iso-induced neurotoxicity. After anesthesia, higher expression of AQP4 was detected in cortex than hippocampus and cerebellum. There was an inverse correlation between increased AQP4 levels and apoptosis/ROS/inflammation. Correlation analysis indicated that AQP4 had a more substantial protective profile against oxidative stress than apoptosis. Remarkably, acutely increased AQP4 against Iso exhibited a more potent neuroprotective effect in cortex, especially frontal cortex. These findings promote further research to understand better the mechanisms underlying anesthesia-induced toxicity in the developing brain.